PENGARUH KEBIJAKAN PENJUALAN TERHADAP LIKUIDITAS PERUSAHAAN PT. XYZ - Saragih, Bongsu (MAJALAH ILMIAH WIDYA, 2012)
Nowadays the progressively development of the business make the various corporate over the world try to increase their effort to developtheir Companies. PT. XYZ intends to develop its company to become a market leader and get the maximal profit. The objective of thisresearch, is to find out whether there are influences between sales policies and return on equity to the increasing of liquidity for the periodof 2006-2010. The method used by primary data collecting (observation and interview) and secondary data by library research. The resultsindicating that: (1) PT. XYZ was able to fulfill the obligation financially, (2) Based on to profitability analysis shows that return on equitygoes up and descend but they are positive valuable altogether, indicating that the company own the abilities.